Estimating winter survival of winter wheat by simulations of plant frost tolerance. (21st September 2017) - Bergjord Olsen, A. K.; Persson, T.; de Wit, A.; Nkurunziza, L.; Sindhøj, E.; Eckersten, H.
Abstract: Based on soil temperature, snow depth and the grown cultivar's maximum attainable level of frost tolerance (LT50c ), the FROSTOL model simulates development of frost tolerance (LT50 ) and winter damage, thereby enabling risk calculations for winter wheat survival. To explore the accuracy of this model, four winter wheat cultivars were sown in a field experiment in Uppsala, Sweden in 2013 and 2014. The LT50 was determined by tests of frost tolerance in November, and the cultivars' LT50c was estimated. Further, recorded winter survival from 20 winter wheat field variety trials in Sweden and Norway was collected from two winter seasons with substantial winter damages. FROSTOL simulations were run for selected cultivars at each location. According to percentage of winter damage, the cultivar survival was classified as "survived, " "intermediate" or "killed." Mean correspondence between recorded and simulated class of winter survival was 75% and 37% for the locations in Sweden and Norway, respectively. Stress factors that were not accounted for in FROSTOL might explain the poorer accuracy at the Norwegian locations. The accuracy was poorest for cultivars with intermediate LT50c levels. When low temperature was the main cause of damage, as at the Swedish locations, the model accuracy was satisfying.